Adenocarcinoma of unknown primary with TP53 gene polymorphism: a rare case report with literature review - Raushan Kumar Chaudhary; Uday Venkat Mateti; Jayaprakash Shetty; Prakash Patil; Vinay C. Sangamesh; Vijith Vittal Shetty (SpringerOpen, 2024)
Abstract Background Cancer of unknown primary (CUP) is an orphan disease generally presented by undifferentiated and aggressive morphological phenotype. The treatment of CUP is solely dependent upon the origin of cancer. Despite extensive diagnostic testing, in most of the cases the primary site remains unidentifiable. Case presentation This case demonstrates a 75-year-old male patient, who initially presented with the complaints of swelling over right side of the neck since 2 months. A cervical lymph node biopsy was taken for immunohistochemistry, which revealed cytokeratin (CK) and CK7 markers to be positive. Computerized tomography (CT) of Thorax showed subcentimetric subpleural nodules in bilateral lungs fields, predominantly in lower lobes (metastatic in nature). A subsequent pulmoCORE 12 gene panel test was recommended, and patient was discharged with tablet gefitinib 250mg and capsule containing vitamins plus minerals. After one month, patient revisited with the pulmoCORE 12 gene test report which revealed polymorphism in TP53. A pathogenic variant of tumor protein p53 (TP53), i.e., p.Glu198Ter (amino acid alteration) and c.592G > T (coding) variant, was detected, which has 17.2% variant allele frequency. There are no treatment guidelines for TP53 mutation; therefore, the patient was treated with injection paclitaxel 70mg and carboplatin 100mg for 12 cycles along with palliative radiotherapy of 20 Gy for 5 fractions. The overall prognosis of patient was found to be favorable. Conclusions There is a need for development of comprehensive guidelines and new molecularly targeted therapies for treatment of CUP which can be tailored for each patient and achieve precise therapeutic outcome.